Determinants Of Obstacles To The Internationalization Of Smes In Developing Countries: A Systematic Review - Citra Dewi Kartika Paksi; Sudarmiatin; Heri Pratikno (International Journal of Business and Quality Research, 2026)
This study conducted a systematic literature review of the latest empirical and conceptual literature on the barriers faced by micro, small, and medium-sized enterprises (MSMEs) in developing countries as they seek to internationalize. Following the PRISMA 2020 protocol, the researchers analyzed peer-reviewed articles published between 2020 and 2025, sourced from the Scopus and Web of Science databases. This review classifies the barriers into two broad categories: internal constraints (financial limitations, human resource deficits, information asymmetry, and marketing weaknesses) and external barriers (institutional weaknesses, regulatory complexity, trade restrictions, and home country effects). The analysis indicates that these barriers rarely operate in isolation. Instead, they form configurations shaped by the interaction between a firm’s resource base, relational capital, and the institutional characteristics of the home country. Findings also indicate that digital capabilities and business networks can mitigate the severity of certain types of barriers, although their effectiveness depends on organizational capacity and the institutional context. This review contributes to the literature on internationalization by consolidating post-pandemic empirical evidence, identifying underutilized theoretical frameworks, and proposing future research directions that emphasize multi-level and context-sensitive analysis of SME internationalization in Southern countries